Permanent stoma after sphincter preservation for rectal cancer. A situation that occurs more often than you might think - Thomas, Flavie; Menahem, Benjamin; Lebreton, Gil; Bouhier-Leporrier, Karine; Dejardin, Olivier; Alves, Arnaud (Frontiers in Oncology, 2023)
Objectives: This study aimed : (i) to assess the cumulative incidence of permanent stoma (PS) after sphincter-preserving surgery (SPS) for rectal cancer (RC) : (ii) to analyse associated risk factors for primary and secondary PS ; and (iii) to compare the long-term survival of patients according to the stoma state. Methods: We conducted a retrospective single-center cohort study based on a prospectively maintained database of SRC patients undergoing SPS from January 2007 to December 2017. Incidence of both primary (no reversal of defunctioning stoma) and secondary (created after closure of defunctioning stoma) PS were investigated. Associations between potential risk factors and PS were analyzed using a logistic regression model. Cumulative survival curve was drawn by Kaplan-Meier method. Results: Of the 257 elligible patients, 43 patients (16.7%) had a PS (16 primary PS and 27 secondary PS) after a median follow-up of 4.8 years. In multivariate analysis, the independent risk factors for primary PS were severe post-operative complications (OR 3.66 ; 95% CI, 1.19-11.20, p=0.022), and old age (OR 1.11 ; 95% CI 1.04-1.18, p=0.001) and those for secondary PS were local recurrence (OR 38.07 ; 95% CI 11.07-130.9, p<0.0001), anastomotic leakage (OR 7.01; 95% CI, 2.23-22.04, p=0.009), and severe post-operative complications (OR 3.67 ; 95% CI, 1.22-11.04, p=0.02), respectively. Both overall survival (OS) and disease-free survival (DFS) were significantly lower in patients with a PS compared with patients with SPS (p < 0.01). Conclusions: This present study suggests that one out of 6 patients has a PS, 5 years after rectal resection with SPS for SRC.